Dekonstruksi dan Rekonstruksi Kitab Suci: Upaya Rasionalisasi Wahyu - Tiur Imeldawati; Warseto Freddy Sihombing (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2023)
Deconstruction and reconstruction of theology is a growing issue in contemporary theology. In a process of study and the author's struggles about theology and how to do theology, this topic is raised and researched through a library research approach. How the characters are affected by the view of deconstruction and how the deconstruction of the biblical texts is carried out. How should theologians position the Bible so that the theological construction that is built is a theology based on correct Biblical studies in accordance with correct hermeneutical steps. True teaching builds on biblical theology, where the study of hermeneutics helps readers discover the intent of the author of the scriptures.